Strategi Satuan Intelijen dan Keamanan (Sat Intelkam) Kepolisian Resor (Polres) Way Kanan Menuju Pelayanan Prima - Fatimah Zahra; Intan Fitri Meutia; Devi Yulianti (Jurnal Administrativa, 2020)
Strategy is a process of administrative drafting to establish ways, programs, objectives, and funds that are set in order to achieve goals. Based on the decision of the National Police Chief No. Pol: Skep / 360 / VI / 2005 June 10, 2005. The Grand Strategy of the Indonesian National Police 2005-2025 divides its substance into three stages, in phase I of 2005-2010 known as the Trust Building, then continued with phase II of 2011-2014 known as Partnership Building, phase III in 2015-2025 is known as strive for excellent. The phase that is currently being carried out is phase III of the 2015-2025 National Police Grand Strategy Strive for Excellence. This stage has the aim of building excellent public service capabilities. This also encourages Way Kanan Resort Police (Polres) in this case concerning the service of Certificate of Good Conduct: Indonesian Police Certificate which is the duty of the Intelligence and Security Unit to perform excellent service to the public is demanded to serve by paying attention to improving service quality through facilities and infrastructure, provision of funds, evaluation of systems and procedures, and development of implementers in order to realize excellent service.